The role of design properties and demographic factors in soft usability problems. (July 2016) - Kim, Chajoong; Christiaans, Henri H.C.M.
Abstract : User-centred design and co-design are nowadays prevalent in product design. However, the number of product returns in consumer electronic industry is continuously increasing. Most complaints are not technical in nature but have to do with non-technical or 'soft' problems. Our study investigates these problems with electronic devices in relation to design properties, characteristics of users and their follow-up (re)actions. The results show that people massively complain about a large variety of products, from computers to e-book readers, and from washing machines to vacuum cleaners. Soft problems are the outcome of the interaction between user characteristics and design properties. Whether users take action upon their complaints also depend on their background. The results have to be translated into a design language. Highlights: The number of product returns in consumer electronic industry is increasing. Most problems with consumer products are not caused by technical failure but are 'soft' in nature. People massively complain about a large variety of consumer electronic products. Results of studies like this are too easily dismissed as just marketing relevant. Designers should be aware of the phenomenon of soft usability problems.